Curriculum Evaluation of Islamic Elementary Teacher Education Programs in Indonesia - Fauzan Fauzan (TARBIYA: Journal of Education in Muslim Society, 2022)
AbstractFrom the Indonesian National Qualifications Framework (KKNI) perspective, each study program should be able to present itself with the “graduate profile” obtained through tracer study activities, feasibility studies and needs analysis in the community. The graduate profile must at least reflect abilities that refer to four aspects of needs (1) attitude, (2) knowledge, (3) general skills; and (4) special skills. The four abilities are translated into a learning outcome (learning outcome) in each course in the study program. Thus, all learning plans or Semester Learning Plans should be based on learning outcomes (learning outcomes) following the needs of the graduate profile. This study aims to evaluate the readiness of the Islamic Elementary Teacher Education study program in Indonesia to implement the current curriculum policy, called the Indonesian National Qualification Framework. This study follows a mixed-method research design by undertaking an evaluation study. Moreover, the data were collected through a literature study, document study, questionnaire, and interview. Twenty-one departments were analysed, involving seventeen state and four private universities. This study provided some noteworthy findings, one of which is to measure how much the readiness of programme directors to implement new policies.AbstrakDari perspektif Kerangka Kualifikasi Nasional Indonesia (KKNI), setiap program studi harus dapat mempresentasikan dirinya sendiri dengan "profil lulusan" yang diperoleh melalui kegiatan studi tracer, studi kelayakan, dan analisis kebutuhan di masyarakat. Profil lulusan harus setidaknya mencerminkan kemampuan yang mengacu pada empat aspek kebutuhan (1) sikap, (2) pengetahuan, (3) keterampilan umum; dan (4) keterampilan khusus. Keempat kemampuan tersebut diterjemahkan menjadi hasil belajar (learning outcome) dalam setiap mata kuliah dalam program studi. Dengan demikian, semua rencana pembelajaran atau Rencana Pembelajaran Semester harus didasarkan pada hasil belajar (learning outcome) mengikuti kebutuhan profil lulusan. Studi ini bertujuan untuk mengevaluasi kesiapan program studi Pendidikan Guru Madrasah Ibtidaiyah di Indonesia untuk menerapkan kebijakan kurikulum saat ini, yang disebut Kerangka Kualifikasi Nasional Indonesia. Studi ini mengikuti desain penelitian campuran dengan melakukan studi evaluasi. Selain itu, data dikumpulkan melalui studi literatur, studi dokumen, kuesioner, dan wawancara. Dua puluh satu departemen dianalisis, melibatkan tujuh belas universitas negeri dan empat universitas swasta. Studi ini memberikan beberapa temuan yang mencolok, salah satunya adalah mengukur seberapa besar kesiapan direktur program untuk menerapkan kebijakan baru.How to Cite : Fauzan. (2022). Curriculum Evaluation of Islamic Elementary Teacher Education Programs in Indonesia. TARBIYA: Journal of Education in Muslim Society, 9(2), 149-162. doi:10.15408/tjems.v9i2.14869.